Operation time as a prognostic indicator on postoperative complications following percutaneous nephrolithotomy - Alireza Pakdel; Abdolreza Mohammadi; Amirreza Shamshirgaran; Ehsan Zemanati Yar; Leila Zareian Baghdadabad; Farshid Alaeddini; Roghayeh Koohi Ortakand; Leonardo Oliveira Reis; Seyed Reza Hosseini; Seyed Mohammad Kazem Aghamir (SAGE Open Medicine)
Objective: We aimed to find an optimal cut-off time for percutaneous nephrolithotomy to prevent complications. Methods: This study enrolled 165 patients aged 18–80 with renal stones ⩾2 cm or ⩾1 cm in lower pole, confirmed via noncontrast computed tomography. Baseline characteristics, stone features, operation time, and anesthesia time were recorded. Logistic regression models were fitted and the ability of the surgery time to predict complications, major complications, and systemic inflammatory response syndrome was evaluated using receiver-operating characteristic curves. Area under the receiver-operating characteristic curve analysis was used as a general indicator of quality. Results: Out of 165 enrolled patients, 157 were analyzed (8 excluded due to follow-up and surgery data issues). The cohort consisted of 115 males (73.2%) and 42 females (26.7%), with a mean (SD) age of 47.4 (12.65) years. Multivariate analysis indicated that longer operation times and lower body mass index correlated with higher complication rates. A cut-off of 65 min for operation time showed 96.8% specificity for predicting complications. Additionally, 47.8% of patients were systemic inflammatory response syndrome positive postprocedure, and operation times were not shown to be predictive of systemic inflammatory response syndrome. Conclusion: Operation time seemed to be a potential risk factor for postpercutaneous nephrolithotomy complications and lowering the operation time could prevent postoperative complications.